Financial policy and central banking in Japan - Cargill, Thomas F.; Itō, Takatoshi; Hutchison, Michael M. (Cambridge, Mass. : MIT Press, 2000)
This book documents the sources of the Japanese economic stagnation of the 1990s, the causes of the financial crises, the slow and initially limited policy response to banking problems, and the reform program that followed. It also evaluates the new financial structure and reforms at the Bank of Japan in the light of the challenges facing the Japanese economy.
Includes bibliographical references (p. [183]-189) and index.
nmn 3/06/13
Loans
Keywords: Banks and banking, Central; Finance; Financial policy - central banking